Optimization Study of Shaft Tubular Turbine in a Bidirectional Tidal Power Station. (24th December 2013) - Ge, Xinfeng; Feng, Yuan; Zhou, Ye; Zheng, Yuan; Yang, Chunxia
Abstract : The shaft tubular turbine is a form of tidal power station which can provide bidirectional power. Efficiency is an important turbine performance indicator. To study the influence of runner design parameters on efficiency, a complete 3D flow-channel model of a shaft tubular turbine was developed, which contains the turbine runner, guide vanes, and flow passage and was integrated with hybrid grids calculated by steady-state calculation methods. Three aspects of the core component (turbine runner) were optimized by numerical simulation. All the results were then verified by experiments. It was shown that curved-edge blades are much better than straight-edge blades; the optimal blade twist angle is 7°, and the optimal distance between the runner and the blades is 0.75–1.25 times the diameter of the runner. Moreover, the numerical simulation results matched the experimental data very well, which also verified the correctness of the optimal results.